Povezanost genskih polimorfizama fibrinogena i inhibitora plazmina, ali ne i faktora zgrušavanja XIII s bolesti koronarnih arterija - Bronic, Ana; Ferencak, Goran; Bernat, Robert; Lenicek Krleza, Jasna; Dumic, Jerka; Dabelic, Sanja (Journal of Medical Biochemistry, 2020)
Background: In the final phase of cloth formation, fibri(noge)n constitutes frame whereas factor XIII (FXIII) active form is responsible for the covalent cross-linking of fibrin fibers and plasmin inhibitor (PI), thus contributing to clot stability. It could be expected that any change of coagulation factors’ structure affects the clot formation and modulate the atherothrombotic risk. The aim was to determine the frequency of four single nucleotide polymorphisms: (i) A>G in codon 312 of the fibrinogen α-chain gene (rs6050, Thr312Ala FGA), (ii) C>T at position 10034 of the 3´untranslated region in the fibrinogen γ-chain gene (rs2066865, 10034C>T FGG), (iii) C>T in codon 564 of the FXIII-A subunit gene (rs5982, Pro564Leu FXIII-A), and (iv) C>T in codon 6 of the plasmin inhibitor gene (rs2070863, Arg6Trp PI) in Croatian patients and their association with coronary artery disease (CAD).Methods: We performed the unrelated case-control association study on the consecutive sample of patients ≥18 years old, who had undergone coronary angiography for investigation of chest pain and suspected CAD. Cases were patients with confirmed CAD (N=201) and controls were the subjects with no CAD (N=119). Samples were genotyped using PCR-RFLP analysis.Results: Observed frequencies of the rare alleles of Thr312Ala FGA, 10034C>T FGG, Leu564Pro FXIII-A and Arg6Trp PI polymorphisms were 21%, 17%, 14%, 20%, respectively. Patients with 10034C> T FGG CC genotype had 3.5 times (95% CI 1.02-12.03) higher adjusted odds for CAD than patients with 10034C> T FGG TT genotype. Patients with Arg6Trp PI CC genotype had 3.86 times (95% CI 1.23-12.12) higher odds for CAD than patients with Arg6Trp PI TT genotype. No difference was observed regarding any other investigated polymorphism,Conclusion: Our finding suggests that 10034C>T FGG and Arg6Trp PI are associated with CAD.